PENGARUH KOMUNIKASI PEMASARAN MELALUI WHATSAPP MESSENGER TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK INDUSTRI RUMAH TANGGA DI KOTA BOGOR - Suraya, Gestio (Jurnal Visi Komunikasi, 2019)
Social media is one of the platforms that is used in addition to the means of communicating as well as facilitating public activity, one of which is shopping. People simply sit or do other work by holding the smartphone, opening the application program, then selecting and ordering the items they want online. This study aims to measure and analyze the influence of Social Media Marketing conducted by Loewi as a home industry entrepreneur in Tajur Village, East Bogor Subdistrict, Bogor City, through WhatsApp Messenger on consumer purchasing decisions. The research method used in this study is an explanative and associative type survey method. The research sample obtained 91 respondents with quantitative data analysis techniques. From the test data analysis found that Social Media Marketing has a significant effect on consumer purchasing decisions on home industry products and the Collaboration dimension in WhatsApp Messenger does not have a significant effect on consumer purchasing decisions on home industry products.